Solidarity on Occasion: The Vancouver Free Speech Fights of 1909 and 1912 - Leier, Mark (Labour/Le Travailleur, 1989)
Abstract The labour and socialist movement of British Columbia before World War One was home to a number of competing tendencies and factions. While the different groups could and did work together on occasion, their relations with each other were often marked by hostility and suspicion. The Vancouver free speech fights of 1909 and 19)2 illustrate dramatically the in-fighting between the Socialist Party of Canada, the Industrial Workers of the World, and the Vancouver Trades and Labor Council. The different approaches of the organizations to the issue of free speech reflect their different ideologies, constituencies, and class strata, and the actions of the SPC suggest that the party was, despite its impossiblist rhetoric, more interested in pragmatic trade unionism and social democracy than revolution. In refusing to put its faith in parliamentary democracy, the IWW demonstrated that it had a more consistent and deeper analysis of capitalist society than most historians have suggested, but this very analysis and the actions consistent with it meant the IWW could be increasingly marginalized and isolated.